FACTORS AND OBSTACLES OF PRIVATE AND PUBLIC SECTOR EMPLOYEES’ DECISION TO RESKILLING AND UP SKILLING ON DIGITAL SKILLS IN BANGKOK AND METROPOLITAN AREA - Intalar, Nuchjarin; Pham, Tai Duc (วารสารปัญญาภิวัฒน์, 2022)
This research studies the factors encouraging employees and obstacles to acquire digital skills in responding to digital transformation in public and private organizations in Bangkok and Metropolitan area. A survey questionnaire was distributed using non-probability and purposive sampling methods. About 425 valid data samples were collected back from June 2020 to March 2021. The binary logistics regression was employed to analyze the factors affecting the development of digital skills. The findings show that megatrend, the rapid change of digital disruption, career advancement, job promotion, and job security are the factors significantly affect the digital skills development. The main obstacles are a lack of financial support and no clear supporting policy from the companies. Apart from common digital skills for routine work, they mainly focus on developing big data analysis, programming, web and app development, and automation skills. Most of the respondents develop their skills by self-study through online channel, on the job training, and attending training organized by private sector with financial support from their companies.